Dead Man's Chest : Exploring the Archaeology of Piracy - Ewen, Charles R., 1956-; Skowronek, Russell K. (Book collections on Project MUSE., 2023)
"A global approach to better understanding piracy through archaeology Featuring discussions of newly discovered evidence from South America, England, New England, Haiti, the Virgin Islands, the Caribbean Sea, and the Indian Ocean, Dead Man's Chest presents diverse approaches to better understanding piracy through archaeological investigations, landscape studies, material culture analyses, and documentary and cartographic evidence. The case studies in this volume include medieval and post-medieval piracy in the Bristol Channel, illicit trade in seventeenth-century fishing stations in Maine, and the guerrilla tactics of nineteenth-century privateers and coastal bandits off the Gulf of Mexico Coast. Contributors reveal the story of a Dutch privateer who saved a ship from a storm only to take control of it, partnerships between pirates and Indigenous inhabitants along the Miskito coast, and new findings on the Speaker-one of the first pirate ships to be archaeologically investigated-in Madagascar. As well as covering shipwrecks and other topics traditionally associated with piracy, several chapters look at pirate facilities on land and cultural interactions with nearby communities as reflected through archival documentation. As a whole, the volume highlights various ways to identify piracy and smuggling in the archaeological record, while encouraging readers to question what they think they know about pirates"--